206k views
0 votes
What is -2/3(3x-4) +3x= 5/6

User Corey G
by
5.4k points

2 Answers

4 votes

Answer:

x= -11/16

Explanation:

Solve for x by simplifying both sides of the equation, then isolating the variable.

User Rxgx
by
5.2k points
0 votes

Answer:


\boxed {x = (7)/(10)}

Explanation:

Solve for the value of
x:


(2)/(3)(3x - 4) + 3x = (5)/(6)

-Use Distributive Property:


(2)/(3)(3x - 4) + 3x = (5)/(6)


2x - (8)/(3) + 3x = (5)/(6)

-Combine like terms:


2x - (8)/(3) + 3x = (5)/(6)


5x - (8)/(3) = (5)/(6)

-Add
(8)/(3) on both sides and the least common multiple of both
6 and
3 is
6. So, convert both fractions
(5)/(6) and
(8)/(3) with the denominator
6:


5x - (8)/(3) + (8)/(3) = (5)/(6) + (8)/(3)


5x = (5)/(6) + (16)/(6)

-Since both fractions have the same denominators, you add them adding the numerators together:


5x = (5 + 16)/(6)


5x = (21)/(6)

-Reduce the fraction to the lowest term by extracting and canceling out the
3:


5x = (21)/(6)


5x = (7)/(2)

-Divide
5 on both sides of the equation. But instead of dividing it, you multiply the denominator
2 by
5:


(5x)/(5) = ((7)/(2) )/(5)


x = (7)/(2 * 5)


\boxed {x = (7)/(10)}

So, therefore, the value of
x is
(7)/(10).

User Tim Hunt
by
5.2k points